Texts and Cultural Change in Early Modern England
X, 254 p.
Keywords: This is a wide-ranging, closely-researched collection, written by scholars from both sides of the Atlantic, on the cultural placement and transmission of texts between 1520 and 1750. Material and historical conditions of texts are analysed, and the range of works is wide, including plays and the Lucrece of Shakespeare (with adaptations, and a discussion of 'reading' playtexts), Sidney's Arcadia, Greene's popular Pandosto (both discussed in the contexts of changing readerships and forms of fiction), Hakluyt's travel books, funerary verse, and the writings of Katherine Parr and Elizabethan Catholic martyrs.